Study of Bone Mineral Density, Serum Sclerostin, and Parathyroid Hormone Levels in Children and Adolescents with Type 1 Diabetes Mellitus - Atalla, Reham Mohammed; Mohamed, Wesam Salah; Hassan, Mona Mamdouh; Erfan, Adel Ali; Elrifaey, Shaymaa Mohamed (Journal of Neonatal Surgery, 2025)
Background: Children and adolescents with type 1 diabetes (T1DM) are more probable to have compromised bone health, as changes in bone mineral density (BMD), serum sclerostin, and parathyroid hormone levels may be involved in skeletal issues. The purpose of this study was to evaluate bone mineral state in children and adolescents with type 1 diabetes. Methods: The present prospective case-control trial was conducted on 75 children and adolescents with ages from 5 to 18 years old, both sexes, having T1DM (Patients group) and 25 healthy children (the control group). Patients were exposed to BMD, serum sclerostin and parathyroid hormone measurement. Results: 25-hydroxyvitamin D (25 OH vit D), serum ionized calcium (Ca), parathormone hormone (PTH), phosphorus and alkaline phosphatase (ALP) were comparable between both groups. BMD was notably reduced in patients’ group than control group (P<0.05). Sclerostin was significantly elevated in diabetic patients than control group (P<0.001). Level of Sclerostin had a positive correlation with diabetes duration, mean glycosylated hemoglobin per year in the diabetic patients (P <0.001). Sclerostin level stated a negative relation with total body and lumbar BMD Z score (P<0.001). Conclusions: There was evidence of low BMD in diabetic patients valued by dual-energy X-ray absorptiometry scan, especially in long standing diabetes with poor glycemic control. Diabetic cases with better glycemic control showed better BMD and sclerostin levels.